2007
DOI: 10.1074/jbc.m609407200
|View full text |Cite
|
Sign up to set email alerts
|

Lysyl Oxidase Interacts with Hormone Placental Lactogen and Synergistically Promotes Breast Epithelial Cell Proliferation and Migration

Abstract: Lysyl oxidase (LOX), an extracellular amine oxidase, catalyzes the cross-linking of collagen and elastin. LOX has been also shown to play an essential role in promoting the invasive and metastatic potential of breast tumor cells. However, the LOXinteracting factors in these processes are not known. In this study, we identified placental lactogen (PL), a member of the growth hormone/prolactin hormone family, as a LOX-interacting partner using yeast two-hybrid screens. PL is normally only expressed in placental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 55 publications
2
20
1
Order By: Relevance
“…A retrospective study of 233 patients with invasive breast carcinomas found that 31% and 25% of invasive ductal and lobular carcinomas, respectively, stained positively for hPL [45], while non-neoplastic breast epithelium was negative for this antigen. More recently, hPL was detected by Western blotting in several breast cancer cell lines [46]. Whereas we did not find previous reports on hPL expression in the human prostate, this issue warrants further investigation.…”
Section: Role Of Placental Lactogen In Hormone-responsive Cancerscontrasting
confidence: 74%
“…A retrospective study of 233 patients with invasive breast carcinomas found that 31% and 25% of invasive ductal and lobular carcinomas, respectively, stained positively for hPL [45], while non-neoplastic breast epithelium was negative for this antigen. More recently, hPL was detected by Western blotting in several breast cancer cell lines [46]. Whereas we did not find previous reports on hPL expression in the human prostate, this issue warrants further investigation.…”
Section: Role Of Placental Lactogen In Hormone-responsive Cancerscontrasting
confidence: 74%
“…A recent study has specified that LOX was not sufficient to induce migration of normal breast epithelial cells. However, the interaction between LOX and placenta lactogen can synergistically promote breast epithelial migration (20). Providing that oral epithelial cells may lack LOX-interacting molecules that caused the silencing of LOX-associated migration regulation, the induction of migration or invasion could be the consequence of propeptide reduction through LOX knockdown.…”
Section: Discussionmentioning
confidence: 99%
“…LOX and HIF-1a act in synergy to promote tumor cell proliferation Both HIF-1a and LOX are known to promote tumor cell growth and survival (9,32). We wanted to determine whether the mutual regulation of LOX and HIF-1a could be involved in colorectal tumor cell growth.…”
Section: Lox Enzymatic Activity Regulates Hif-1a Expression In Hypoxiamentioning
confidence: 99%
“…LOX is a copper-dependent amine oxidase that catalyzes the cross-linking of collagen and elastin in the extracellular matrix (ECM), thereby increasing insoluble matrix deposition and tensile strength (8). LOX has been shown to enhance tumor cell proliferation and invasion (5,9,10), particularly by increasing ECM stiffness (11).…”
Section: Introductionmentioning
confidence: 99%